Investigation of the histoarchitecture of bovine pericardium as the primary material used in reconstructive surgery and bioprosthesis - A. I. Zvyagina; K. V. Pyatina; V. V. Minaiychev; M. I. Kobyakova; Ya. V. Lomovskaya; A. S. Senotov; A. Yu. Teterina; I. S. Fadeeva (Вестник трансплантологии и искусственных органов)
Objective: to study the composition and topology of the extracellular matrix (ECM) of bovine pericardium and to identify the best tissue areas suitable for the fabrication of bioprosthetic heart valves (BHVs). Materials and methods. The pericardium samples of healthy sexually mature bulls were studied; the native pericardium was divided into three experimental groups: core tissue (BP-CT group), heart base (BP-HB) and connective ligament base (BP-CL). Scanning electron microscopy was used to examine the structure of the pericardial surfaces (p. serosum and p. fibrosum), while differential histochemical analysis was used to study the topology of various pericardial regions, with identification and quantification of the main constituents of the extracellular matrix (ECM) (collagen, elastin, lipids, and glycosaminoglycans). Quantification was performed by bioimaging and digital analysis of histological images using the ImageJ software. Results. The BP-CT group had the lowest cellular density and, consequently, DNA content (369.75 ± 23.12 ng/mg), in addition to having the most homogeneous, predominantly collagenous (95.6 ± 2.9%) matrix composition with minimal lipid (2.6 ± 1.5%), glycosaminoglycan (0.68 ± 0.7%) and elastin (3 ± 2.4%) content. The BP-CL group had the highest levels of elastin and glycosaminoglycans (27.8 ± 3% and 17.5 ± 0.6%, respectively), while the BP-HB group had the highest lipid content (21.2 ± 2.7%.). On the p. serosum side, the ECM composition was noticeably homogeneous, while elastin fibers, glycosaminoglycans, and lipid clusters were predominantly found on the p. fibrisum side, indicating the natural polarity of the material, which should be considered when fabricating biomaterials. Conclusion. The findings in this study revealed that bovine pericardial topology varied depending on the tissue area. Only the main pericardial tissue can be used to create BHVs, as evidenced by the comparative homogeneity of ECM composition and relatively low cellular density. The high content of elastin, glycosaminoglycans and lipids in specific pericardial tissue areas (the BP-HB and BP-CL groups) suggests that either this layer needs to be removed more thoroughly during implant fabrication (e.g., by selective purification techniques) or these pericardial tissue areas should be used where heterogeneity of the composition is desired (e.g., in maxillofacial and orthopedic surgery).